DETERMINANTS OF INVESTORS DECISION MAKING: A CASE STUDY IN THE INDONESIA STOCK EXCHANGE (IDX) - Thohiri, Roza; Yuni, Revita; Hastuti, Pebri (Journal of Community Research and Service, 2020)
Inflation in Indonesia tends to perform an issue for investors with regards to the yield value from the investment instrument they put in. The capital market in Indonesia is currently promoting stake in shares with the slogan "let's save shares," which at this time, the returns continue to improve. The purpose of this research to identify the characteristics of stock investors in the IDX, analyze the decision making process of stock investors to choose stocks in the Indonesian stock exchange. It is also intended to find out factors influencing investors to engage in trading activities on the IDX. The data analysis technique used is the validity and reliability of the questionnaire given to respondents, descriptive analysis, and factor analysis. The results of the study found that the validity and reliability of this study are valid and reliable. In the decision-making stage of stock purchase, it is obtained the introduction of problems with sources of income as the primary goal to get capital gains and dividends. Most information searches come from the internet with information searching time around 1-2 days. In evaluating alternatives in making purchases, it turns out stock is the leading choice, with the main consideration being the profit potential. In determining the purchase decision, all respondents have planned well, and themselves have the most influence with the decision making time ranging from 2-7 days. Post-purchase behavior respondents were satisfied with their choice, and the waiting time to get benefits ranged from 3-4 weeks. This research shows, four factors influence investors in buying and selling shares on the IDX, namely information factors, preferred stock factors, market activity factors, and risk-limiting factors. The most influential factor is the information showing the highest percentage of 46.52 percent, among other observed factors. Keywords: Capital Market, Investors, Factor Analysis, Decision Making.